2020
DOI: 10.1007/s00392-020-01604-1
|View full text |Cite
|
Sign up to set email alerts
|

The association of body mass index with long-term clinical outcomes after ticagrelor monotherapy following abbreviated dual antiplatelet therapy in patients undergoing percutaneous coronary intervention: a prespecified sub-analysis of the GLOBAL LEADERS Trial

Abstract: Background The efficacy of antiplatelet therapies following percutaneous coronary intervention (PCI) may be affected by body mass index (BMI). Methods and results This is a prespecified subgroup analysis of the GLOBAL LEADERS trial, a prospective, multicenter, open-label, randomized controlled trial in an all-comer population undergoing PCI, comparing the experimental strategy (23-month ticagrelor monotherapy following 1-month dual antiplatelet therapy [DAPT]) with a reference regimen (12-month aspirin monothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Obesity is associated with an increased prevalence and incidence of many noncommunicable chronic diseases (NCDs) including end-stage kidney disease [1,2], type II diabetes [3], cardiovascular disease [3,4], atrial fibrillation [5], nonalcoholic steatohepatitis [6], and colorectal cancer [7][8][9][10]. However, among populations with these NCDs the risk of mortality is often lower for those with obesity [1][2][3][4][5][6][7][8][9][10]. It is also associated with a lower risk of mortality among elderly people and those who are critically ill [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is associated with an increased prevalence and incidence of many noncommunicable chronic diseases (NCDs) including end-stage kidney disease [1,2], type II diabetes [3], cardiovascular disease [3,4], atrial fibrillation [5], nonalcoholic steatohepatitis [6], and colorectal cancer [7][8][9][10]. However, among populations with these NCDs the risk of mortality is often lower for those with obesity [1][2][3][4][5][6][7][8][9][10]. It is also associated with a lower risk of mortality among elderly people and those who are critically ill [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In line with previous studies, the ‘obesity paradox’ was again observed with a reverse J-shape association between mortality risk and body mass index (BMI). 19 There was no treatment effect on the primary endpoint in patients with low (<27 kg/m 2 ) or high (≥27 kg/m 2 ) BMI. In patients with ACS, however, the primary endpoint was significantly reduced with the experimental strategy in patients with a BMI <27 kg/m 2 , which was not observed in those with a BMI ≥27 kg/m 2 .…”
Section: Section 2: Pre-specified and Exploratory Analyses From Global Leadersmentioning
confidence: 84%
“…The prespecified [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ] and selected post-hoc analyses [ 57 , 58 , 59 , 60 , 61 ] performed by the GLOBAL LEADERS investigators for exploring the effect size of the intervention on different subgroups are shown in Table S1 .…”
Section: P2y 12 Monotherapy Versus Dapt After Pcimentioning
confidence: 99%